Complexity of Conflict and Resolution in the PT. HMBP 2023 Case Related to the Failure to Realize Plasma Plantations and Its Impact on Indigenous Communities from the Perspective of Criminal and Civil Law - Alireja, Irfan M N; Joko Setiono; Hamid, Supardi (Greenation Publisher & Yayasan Global Resarch National, 2025)
The conflict between PT. HMBP and the indigenous community of Bangkal Village in Central Kalimantan reflects the complexity of agrarian issues that simultaneously involve aspects of both criminal and civil law. The problem began with PT. HMBP’s failure to fulfill its obligation to develop plasma plantations covering 20% of the total managed land, as mandated by Government Regulation No. 26 of 2021 and Central Kalimantan Provincial Regulation No. 5 of 2011. Tensions peaked in October 2023 when the community staged a blockade of 1,175 hectares of land outside the company’s concession (HGU), which led to clashes with security forces and resulted in fatalities. This study uses a normative juridical approach by examining relevant laws and regulations as well as principles for the protection of indigenous peoples’ rights. The analysis reveals potential violations of criminal law, both in terms of the repressive actions by authorities and the company’s negligence in fulfilling its legal obligations. From a civil law perspective, PT. HMBP could be sued for breach of contract and unlawful acts that harmed the community. Furthermore, violations of human rights—particularly the right to land and the right to life, emerge as key concerns, calling for the involvement of the National Commission on Human Rights (Komnas HAM) and the application of restorative justice approaches. This study recommends regulatory reinforcement, enhanced mediation roles by local governments, and stronger protections for indigenous rights in the context of agrarian conflicts. It emphasizes the importance of fair, accountable, and human-centered law enforcement in resolving similar disputes in the future.